Word Formation Process in Adeleâ€™s â€œ30â€ Song Album: A Comprehensive Morphological Analysis - Fitria Aprilia; Neisya; Fitri Sonia (RETORIKA: Jurnal Ilmu Bahasa, 2023)
This research aims to analyze comprehensively morphological process of word formation in song album â€œ30â€ by Adele. Word formation focuses on the process of making or constructing new words based on other words or morphemes. Descriptive qualitative method was applied since the data were in the form of words, phrases, and sentences. The theory proposed by Yule (2017) was used in analyzing the word formation process. The data of this research were 12 songs contained in song album â€œ30â€ by Adele. Based on the analysis, it was found that there were 6 types out of 14 types of word formation process in song album â€œ30â€ by Adele. Specifically, this research found 44 data of word formation process. There were 6 data of compounding, 1 data of clipping, 1 data of backformation, 1 data of acronyms, 2 data of derivation and 33 data of prefixes and suffixes. Prefixes and suffixes were concluded as the most dominant type of word formation process that was found in song album â€œ30â€ by Adele.